Recurrent Breast Cancer in a Patient with a Ventriculoperitoneal Shunt - Libby R. Copeland-Halperin; Robert A. Cohen (Case Reports in Surgery)
We report a case of a patient with recurrent infiltrating ductal carcinoma of the breast encasing a ventriculoperitoneal shunt. We also review the current literature regarding reports of breast malignancy around a ventriculoperitoneal shunt, as well as the potential relevance of such shunts to the preoperative evaluation and management of patients with breast cancer.